Analisis Peningkatan Pelanggan di Bengkel PT. Kharisma Sentosa Surabaya Minggu ke 3 Juni 2025 - Nurul Hariyanto; Bambang Karnain P; I Gede Wiyasa (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This proposal presents the final report of the field work lecture (KKL) regarding the analysis of customer increase at the PT. Kharisma Sentosa Surabaya workshop on the 3rd week of June 2025. The aim is to determine the factors causing an increase or decrease in customers and to improve the quality of service at the workshop. A qualitative approach is used to understand the factors causing an increase in customers through interviews and observations. This report provides insight into service management and company strategy. The results of the study indicate that the main factors influencing the increase in customers at the PT. Kharisma Sentosa workshop are service quality, competitive prices, and customer trust in the workshop's reputation. In addition, the existence of promotions and recommendations from satisfied customers also play a role in attracting new customers. Conversely, the decrease in the number of customers is caused by problems such as long service waiting times, lack of clear communication regarding prices and schedules, and complaints regarding the quality of vehicle repair results. Based on these findings, this report provides insights into the importance of effective marketing strategies and improving service quality to maintain customer loyalty.